A qualitative assessment of alternative eradication strategies for African swine fever in the Dominican Republic - Schambow, Rachel; Reyes, Raysa; Morales, Jose; Diaz, Alan; Perez, Andres M. (Frontiers in Veterinary Science, 2022)
Since its recent detection in July 2021, the reintroduction of African swine fever(ASF) in the Dominican Republic (DR) has generated much discourse on various measures for its effective control. Strategies range from complete depopulation of the swine population, as was done in 1978, to a system of passive surveillance with endemicity, with many in-between. Currently, ASF-decision makers need a peer evaluation and comparison and contrast of these potential strategies that incorporates both private and public perspectives. To achieve this, we used strengths, weaknesses, opportunities, and threats (SWOT) analysis to evaluate three different theoretical ASF control scenarios with the aim of contributing evaluations of alternatives strategies to mitigate the epidemic’s impact. These included total depopulation of all pigs in the DR, partial depopulation, and continuation of current control measures. Relevant experts from the DR private swine industry were identified through “snowball sampling" techniques. Five experts completed the SWOT questionnaire and additional questions considering aspects of financial cost, social impact, feasibility, animal welfare, and regional policy. The summarized responses were presented to the full group of experts initially nominated for final review and later to representatives of the DR government. The SWOT analysis highlighted that although there are certain benefits associated with each of the proposed strategies, there are also important drawbacks and disadvantages for all. This analysis is a tool for facilitating cooperating between the private-public industries, and ultimately it supports the development of strategies that will reduce ASF burden in the DR in a way suitable for all relevant stakeholders.